Institutions and financial development: Comparative analysis of developed and developing economies - Fernanda Cigainski Lisbinski; Heloisa Lee Burnquist (EconomiA, 2024)
Purpose – This article aims to investigate how institutional characteristics affect the level of financial development of economies collectively and compare between developed and undeveloped economies. Design/methodology/approach – A dynamic panel with 131 countries, including developed and developing ones, was utilized; the estimators of the generalized method of moments system (GMM system) model were selected because they have econometric characteristics more suitable for analysis, providing superior statistical precision compared to traditional linear estimation methods. Findings – The results from the full panel suggest that concrete and well-defined institutions are important for financial development, confirming previous research, with a more limited scope than the present work. Research limitations/implications – Limitations of this research include the availability of data for all countries worldwide, which would make the research broader and more complete. Originality/value – A panel of countries was used, divided into developed and developing countries, to analyze the impact of institutional variables on the financial development of these countries, which is one of the differentiators of this work. Another differentiator of this research is the presentation of estimates in six different configurations, with emphasis on the GMM system model in one and two steps, allowing for comparison between results.